2014
DOI: 10.3171/2013.9.jns13788
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of predicting survival in individual patients with cancer

Abstract: Object Estimating survival time in cancer patients is crucial for clinicians, patients, families, and payers. To provide appropriate and cost-effective care, various data sources are used to provide rational, reliable, and reproducible estimates. The accuracy of such estimates is unknown. Methods The authors prospectively estimated survival in 150 consecutive cancer patients (median age 62 years) with brain metastases undergoing radiosurgery. They recorded cancer type, number of brain metastases, neurological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(63 citation statements)
references
References 33 publications
0
61
1
1
Order By: Relevance
“…33 Compared to studies with a similar median survival, we find that the accuracy estimates reported here are within the range of previously published values. 33 Chow et al 10 found that providers tended to be less accurate and overestimated survival to a greater extent than we report (average overestimate of 12.3 weeks vs. our finding of 6.8 weeks) and Kondziolka et al 34 found that providers were more accurate in predicting survival to within a year (82% vs. our finding of 74% of physicians predicting life expectancy to within a year). Studies that use the surprise question (i.e., would you be surprised if this patient died within a year?)…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…33 Compared to studies with a similar median survival, we find that the accuracy estimates reported here are within the range of previously published values. 33 Chow et al 10 found that providers tended to be less accurate and overestimated survival to a greater extent than we report (average overestimate of 12.3 weeks vs. our finding of 6.8 weeks) and Kondziolka et al 34 found that providers were more accurate in predicting survival to within a year (82% vs. our finding of 74% of physicians predicting life expectancy to within a year). Studies that use the surprise question (i.e., would you be surprised if this patient died within a year?)…”
Section: Discussioncontrasting
confidence: 51%
“…38 Finally, the data presented here were collected from 2002 to 2011, however, there is no evidence to suggest that the accuracy of physician estimates has changed substantially in the interim. 34 In summary, this study finds that 74% of physician lifeexpectancy estimates are accurate to within a year, and the accuracy of prognostic estimates may be improved if clinicians take into account the McGill Quality-of-Life questionnaire and the Charlson Comorbidity Index. Although physician-estimated life expectancies are often considered inaccurate, our estimates were similar to previously reported values and provided patients with a significantly more realistic understanding of their prognosis and a higher quality of care at the end of life.…”
Section: Discussionmentioning
confidence: 70%
“…3 Although the use of BM-specific prognostic scores provides valuable information for patient management and has been widely adopted, especially in the context of clinical trials, the prediction of survival times is inaccurate and needs improvement. 4 Laboratory parameters routinely assessed in clinical practice have been shown to correlate with patient outcome in several diseases including cancer. [5][6][7][8] Therefore, we hypothesized that standard hematologic and serum biochemical parameters could be valuable for prediction of survival in BM patients.…”
Section: Introductionmentioning
confidence: 99%
“…More relevant to this chapter, Kondziolka et al (2014) performed an interesting prospective study. Data of 150 consecutive cancer patients with BM undergoing SRS were recorded (including histology, number of BM, extracranial disease status, age, KPS).…”
Section: How Should We Prognosticate Patients With Bm?mentioning
confidence: 99%